The influence of security guaranteeing the sanctity of a packed food product on packaging perceiving by younger and older consumers - Popek, Stanisław; Świda, Jarosław (Engineering Sciences And Technologies, 2015)
The aim of the research is to determine potential differences in perceiving food products packaging with the tamper evident protection by consumers belonging to two age groups (young – up to 25 years old and older ones aged over 60). The empirical research connected to perceiving protection guaranteeing sanctity of the packed product by consumers, has been conducted by the direct questionnaire interviews on the sample n = 348 of the south-east Poland inhabitants. The results of the research about the experiences and feelings concerning the securities, which guarantee the sanctity of the food products packaging can be a feedback for manufactures in the context of differentiation of the packaging aimed at different consumer age groups
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2015, Nr 1 (16), s. 61-71
Keywords: consumer perception; tamper evidence; packaging; percepcja konsumenta; zabezpieczenie gwarantujące nienaruszalność zapakowanego produktu; opakowanie